PERAN ORANG TUA DALAM PENDIDIKAN SEKS PRANIKAH PADA REMAJA - Eka Ananda Lintang Savitri; Aldi Saputra; Fikri Ardiansyah; Firsty Oktaria Grahani (Pusat Studi GESI - UWP, 2023)
Adolescence begins with puberty, which is a time of physical changes and physiological functions such as the maturity of sexual organs. The role of parents is very important to educate, supervise, describe how to solve problems and be role models and set a good example for adolescents. This study aims to describe how the role of parents in sex education and how parents understand premarital sex. The method used is a qualitative method in the form of data collection, using interviews and observation. The subjects in the study were three elderly people. The results showed that children have begun to understand the meaning of sex, understand reproductive organs, ethics in getting along, and can explain the dangers of premarital sex and its effects including venereal diseases. The conclusions obtained are as follows: (1) Parents' understanding of sex includes biological, psychological and cultural needs. (2) How to communicate sex issues to children can be done without any special time, by taking advantage of momentum, conveyed clearly unambiguously. Sex education is also given according to the needs of children and without having to start with an event. (3) The role of parents in sex education includes the distribution of duties, monitoring in sexual matters. (4) Children respond positively to sex education given by parents if the atmosphere is conducive, on the contrary, children's responses become negative if the moment of providing sex education is not appropriate (5) Sex education materials include sex differences, social ethics, and sexual diseases.Kata kunci : adolescents, the role of parents, sex education.